COMPARATIVO DE CUSTO DIRETO DO SISTEMA WOOD FRAME E PAREDES DE CONCRETO MOLDADAS IN LOCO PARA HABITAÇÕES DE INTERESSE SOCIAL - Santos Filho, Roberto; Salomão, Maria Cláudia; Arantes, Ismara S. C. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In cities with accelerated growth, the residential deficit has been fixed with the use of new constructive systems. In that way, this civil engineering coursework aims to study the viability of wood frame system as a new option for construction of low budget houses. The wood frame system was compared to concrete wall system. An estimating cost of walls, structure, roof and foundation of both systems was developed to study the economic viability of wood frame system. The wood frame constructive system has presented a higher cost per square meter when compared to the concrete walls system, with some considerations.